The impacts of digital transformation on fisheries policy and sustainability: Lessons from Timor-Leste - Tilley, Alexander; Dam Lam, Rodolfo; Lozano, Denise; Dos Reis Lopes, Joctan; Da Costa, Dede; Belo, Maria; Da Silva, Joaquina; Da Cruz, Gilberto; Rossignoli, Cristiano (Elsevier, 2024)
Digital technologies are transforming how we monitor and manage natural resources, by speeding up data-driven decision-making. Still, to date, there is scant evidence of their impacts on environmental sustainability. In fisheries, a digital record of landings represents enormous potential for sustainable food production, resource management, and livelihoods, by making information about fish production and price available to all. To fill a gap in information and understanding about fisheries in Timor-Leste at the time, and to inform decision-making to renew outdated fisheries legislations and strategies, the ‘Peskas’ system was developed and piloted in Timor-Leste in 2017. Peskas was designed to collect, analyse and display small-scale fisheries data in near real-time to improve fisheries management through real-time data-driven policymaking. Using targeted interviews in key stakeholder groups, we assessed the progress made toward this goal through three different pathways over a six-year period: i) capacity building; ii) partnership and collaboration; and iii) sustainable resource management. Results showed that the formal Government adoption of Peskas was a tipping point that catalysed greater intragovernmental collaboration, as well as between government and communities, and brought new investment into the fisheries sector. However, Peskas has had minimal impact on the development of new regulations to date. We discuss reasons for this, such as an inadequate fisheries legal framework and wider capacity gaps and draw broader recommendations for how to leverage digital transformation for positive change in fisheries sustainability.